Opposing roles of glutaminase isoforms in determining glioblastoma cell phenotype. (September 2015) - Szeliga, Monika; Albrecht, Jan
Highlights: Distinct mammalian glutaminase (GA) isoforms are coded either by Gls or Gls2 gene. Cell proliferation-promoting GA coded by Gls is overexpressed in mammalian tumors. GA arising from GLS2 (GAB) is specifically absent in human malignant gliomas. Joint GAB induction and GLS silencing radically suppresses glioma growth in vitro . Joint GAB induction and GLS silencing may aid glioma therapy in human patients. Abstract: Glutamine (Gln) and glutamate (Glu) play pivotal roles in the malignant phenotype of brain tumors via multiple mechanisms. Glutaminase (GA, EC 3.5.1.2) metabolizes Gln to Glu and ammonia. Human GA isoforms are encoded by two genes: GLS gene codes for kidney-type isoforms, KGA and GAC, whereas GLS2 codes for liver-type isoforms, GAB and LGA. The expression pattern of both genes in different neoplastic cell lines and tissues implicated that the kidney-type isoforms are associated with cell proliferation, while the liver-type isoforms dominate in, and contribute to the phenotype of quiescent cells. GLS gene has been demonstrated to be regulated by oncogene c-Myc, whereas GLS2 gene was identified as a target gene of p53 tumor suppressor. In glioblastomas (GBM, WHO grade IV), the most aggressive brain tumors, high levels of GLS and only traces or lack of GLS2 transcripts were found. Ectopic overexpression of GLS2 in human glioblastoma T98G cells decreased their proliferation and migration and sensitized them to the alkylating agents often used in the chemotherapy of gliomas. GLS silencing reduced proliferation of glioblastoma T98G cells and strengthen the antiproliferative effect evoked by previous GLS2 overexpression.